Information policy of the people's Republic of China in Xinjiang-Uyghur autonomous region - Elmira Kamilevna Khabibullina, Dmitriy Aleksandrovich Balakin, Alfiya Rafisovna Alikberova, (Opción, 2019)
The purpose of the article is to study and analyze the information policy of China in the Xinjiang Uyghur autonomous region, as one of the striking examples of information policies' implementation. The leading approaches to the study of this problem are the system-structural approach and comparative-comparative analysis. The main result of the study is the identification of new mechanisms of influence, features of digital diplomacy and information policy of the PRC. Also, the conclusion was made that at present China needs to focus on the formation of a positive image in the global information field as a single, integral state.